Satisfaction of the disputing parties as consumers towards reconciliation process at the marriage tribunal in Malaysia: An empirical study - Abdul Hak, Nora; Rahmat, Nur Ezan (2017)
The conciliatory bodies appointed under section 106 of the Law Reform (Marriage and Divorce) 1976 Act are not effective while, the existing legal provisions concerning reconciliation process are not adequate to reconcile the matrimonial disputes of non-Muslims. This paper starts with the interpretation on descriptive statistics of demographic characteristics of the respondents, followed by test of the knowledge of the respondents on the law, satisfaction of the respondents with the process of reconciliation and lastly, on the outcome of the process. Every part of the questionnaires was tested by using the normality test to determine if a data set is well-modelled by a normal distribution. The statistical methods employed in this study range from frequency distribution, descriptive statistics, and non-parametric analysis. The finding shows that although the respondents are quite satisfied with the reconciliation session, but it still fails to reconcile the disputing parties. Suggestions for improvement of the existing practice are discussed.